Sharia-Based Abr Wastewater Treatment Plant Design to Support Clean Culture Achievement in Labuhan Tarok Village, Meukek District, South Aceh - Astuti*, Widi; Purboseno, Sentot (Riwayat: Educational Journal of History and Humanities, 2024)
Aceh Selatan is the oldest district in Aceh Province, located on the edge of the Banda Aceh Medan west cross highway consisting of mountainous areas, lowlands, and water areas (Hindia Ocean). The problem at this time is that 54% of the people of South Aceh Regency do not have proper access to latrines and drainage channels, which are the target for receiving domestic wastewater. There is no public awareness of the importance of providing and maintaining domestic wastewater facilities and infrastructure. This research aims to sustainably carry out regional-scale domestic wastewater management based on Maqashid Syariah. The method used in the research is to determine the target of wastewater handling in South Aceh Regency until 2040 to determine the development model and strategy. Meanwhile, the zoning method was used to determine the planning area. Labuhan Tarok Village, Meukek District, South Aceh Regency, is one of the villages in urgent priority scale wastewater treatment with the An Aerobic Baffled Reactor (ABR) model. The reduction of BOD, COD, and TSS can be made with this treatment model in accordance with the Quality Standard of Peraturan Menteri Lingkungan Hidup dan Kehutanan No. 68 of 2014 and accordance with Permen PUPR No.4 of 2017, concerning the Implementation of Domestic Waste Water Management Systems.